STUDI KOMPARASI MOTOR BAKAR 6 TAK DENGAN SIKLUS DUA KALI PENGAPIAN MENGGUNAKAN BAHAN BAKAR PERTAMAX DAN ETANOL - Elandi Elandi; Eko Siswanto; Agung Sugeng Widodo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
The six-stroke combustion engine is a refinement of the four-stroke machine by adding two strokes of the four-stroke combustion engine. The two steps in question are the second compression stroke and the second expansion stroke. The method used is an experimental research method. This study aims to obtain the performance value and exhaust gas emission values ​​for Pertamax and Ethanol fuels on a six-stroke engine. The fuel used is Pertamax fuel with a purity of 100% and Ethanol with a purity of 99.7%. Based on the results of research, analysis, and discussion, the performance of a six-stroke combustion engine with two cycles of ignition with Pertamax and Ethanol fuel is concluded that the average torque of Pertamax fuel is 1.07% higher than Ethanol fuel. The average adequacy of Pertamax fuel is 1.27% higher than Ethanol fuel. The combustion efficiency of the Pertamax fuel six-stroke motor is 1.06% less than ethanol fuel, the cycle work (Wnet) of the Pertamax fuel six-stroke engine is 1.07% higher than that of ethanol fuel, the thermal efficiency (ηth) of the Pertamax fuel six-stroke engine is comparable to that of ethanol fuel while the fuel efficiency (ηf) of the six-stroke ethanol fuel engine is 1.09% higher than the pertamax fuel. The exhaust gas emission test results for Pertamax fuel CO are 21.2% higher than ethanol fuel. CO2 emissions from Pertamax fuel are 1.56% less than ethanol fuel, and HC exhaust emissions from Pertamax fuels are 3.7% higher than ethanol fuels.